If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -64 = 90 Reorder the terms: -64 + 14x = 90 Solving -64 + 14x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '64' to each side of the equation. -64 + 64 + 14x = 90 + 64 Combine like terms: -64 + 64 = 0 0 + 14x = 90 + 64 14x = 90 + 64 Combine like terms: 90 + 64 = 154 14x = 154 Divide each side by '14'. x = 11 Simplifying x = 11
| 20x-3=71 | | x^2+12x=-2 | | -52x-18=86 | | x^3+3x^2-2x=0 | | x(x)+7x+6=0 | | x(x)-2x+1=0 | | -4x+17=86 | | 4p(p)+8p=0 | | 10x-30=-80 | | (2b+1)(2b+1)=25 | | -5x+6y=69 | | 15x+17=-73 | | -6x-63=-75 | | -6-63=-75 | | x^3-6x-9=0 | | 3(x^2)+32x+45= | | x(x)-x-20=0 | | 30(x^2)+37x+10= | | 16=4(x-5)2 | | x(x)+12x-13=0 | | 8xy-120(x^2)(y^4)= | | x(x)-8x+12=0 | | (t+2)(t+2)=4 | | (t+2)2=4 | | 28-5x=4x+8 | | y=12x^2+203x+7 | | (6x+5)(4x+8)= | | 4x^2+6x+7=0 | | 3(n+1)=2(n+4) | | (-6x^2+10x+8)+(-8x^2+2x+6)= | | x^2+3x-x-3=0 | | 4x^2+7x-57= |